(3GdEjeGf (B:s (3eLdI TgQjI (B/s - (3GdfGOj GdKbGaj Gdbhej (B((3GdchjJ (B)s; (3GdfGOj GdKbGaj Gdbhej (B((3GdchjJ(B)s ((3GdchjJ (B:s (3GdfGOj GdKbGaj Gdbhej ,s (3eQcR GdHMhK hGdOQGSGJ GdchjJjI , s, 1953)
(3aj eNJda GdehVhYGJ(B.s
Keywords: (3GdOhQjGJ GdYQHjIs -- (3OhQjGJ s; (3KbGaI ELJeGYjI s -- (3OhQjGJ s